Problem Based Learning Model Assisted by Renderforest Video Animation on Mathematics Learning Outcomes - Intan Permata Sari; Achmad Fathoni (International Journal of Elementary Education, 2022)
Teachers need to be more able to package learning models and media in mathematics lessons, causing students to feel more confident and energized in learning. This study aims to analyze the effect of using the problem-based learning model assisted by renderforest video animation media on students' mathematics learning outcomes in fourth-grade elementary school building materials. This study uses a quantitative experimental approach. This type of research uses a quasi-experimental design, using a total sample of 28 students. Data collection techniques are used through learning achievement tests and documentation. The technique used to analyze the data is the T-test. The analysis results show that the average post-test score for the control class is 77 in the adequate category, the minimum score is 55, and the maximum is 81. The average post-test learning outcomes for the experimental class are 86 in the good category, the minimum score is 80, and the maximum is 92. Results Data analysis showed an effect of using the problem-based learning model assisted by renderforest video animation media in improving the mathematics learning outcomes of geometric materials in grade IV S students. It was concluded that the problem based learning model assisted by renderforest video animation media could improve mathematics learning outcomes in elementary school students.